2019
DOI: 10.3390/ijerph17010122
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Sporting Destinations through Improving Tourists’ Mental and Physical Health in the Tourism Environment: The Case of Korea

Abstract: The purpose of this study was to explore structural relationships between emotional experiences, novelty seeking, tourist satisfaction, and destination loyalty in the context of active sport tourism. The study emphasizes the mediating effect tourist satisfaction has on the relationship between emotional experiences and destination loyalty. The validities and reliabilities of the measures used were examined through confirmatory factor analysis (CFA) and correlation analysis using 230 domestic and international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
0
22
1
4
Order By: Relevance
“…According to Kaplanidou et al [15] (p. 550), most active sport tourists who participated in a focus group interview mentioned that "It was exciting", "It [the event] was an accomplishment", "I prepare more for cycling events, but it was still a challenge to get through some of the day", "It was a lot of fun", and "There is a certain amount of pride doing it". It can be inferred from these statements that active sport tourists are likely to attach special meanings to and develop a deeper emotional connection with sporting events and destinations to which they have traveled and/or participated [14,16,17]. Therefore, promotion of recurring participatory sports events would be a good strategy for a destination in bringing a steady stream of visitors, considering previous findings on the positive relationship between emotions and behavioral intention [13].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…According to Kaplanidou et al [15] (p. 550), most active sport tourists who participated in a focus group interview mentioned that "It was exciting", "It [the event] was an accomplishment", "I prepare more for cycling events, but it was still a challenge to get through some of the day", "It was a lot of fun", and "There is a certain amount of pride doing it". It can be inferred from these statements that active sport tourists are likely to attach special meanings to and develop a deeper emotional connection with sporting events and destinations to which they have traveled and/or participated [14,16,17]. Therefore, promotion of recurring participatory sports events would be a good strategy for a destination in bringing a steady stream of visitors, considering previous findings on the positive relationship between emotions and behavioral intention [13].…”
Section: Introductionmentioning
confidence: 89%
“…Likewise, the current study seeks to understand behaviors of active sport tourists, who can be referred to as those travelers who are seeking sport-related event participation opportunities at a destination. As they do for general tourists, several authors have suggested that emotions are closely related with before, during, and after trips of active sport tourists [14,15]. In other words, sporting events such as marathon, cycling, badminton, table tennis, climbing, hiking, skiing, windsurfing, and canoeing events evoke emotional responses (e.g., exciting, enjoyment, happy, self-fulfillment, accomplishment, challenge, and pride) of active sport tourists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an important relationship between ecotourism and environment. Moreover, literature also discussed the relationship between tourism and environment (Jeong, Kim, & Yu, 2020), however, the relationship between ecotourism and environment is not discussed in relation to the hotels and restaurants. Therefore, this study has significant contribution to the literature of hotels and restaurants in respect to the tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is one of the important sources of revenue generation. Literature also shows the significant importance of health tourism (Jeong, Kim, & Yu, 2020;Wilkinson, 2020). However, health tourism is varying from country to country based on the services of health sector.…”
Section: Introductionmentioning
confidence: 99%